Evaluation of the impact of the agricultural insurance program of PCIC on rice producers in region VI - Gay Defiesta; Hanny John Mediodia (Philippine Institute for Development Studies (PIDS), 2016)
Rice is the most important agricultural commodity in Western Visayas, being one of the top producers of rice in the country. Rice production, however, is a highly risky venture in disaster-prone Philippines. Majority of the rice farms in the region are small farm holders who are more vulnerable to crop damages and diseases. To reduce small farmers' vulnerability, the government provides social insurance through the Philippine Crop Insurance Corporation (PCIC). Crop insurance is viewed as a risk management tool that can stabilize farmers' income and consumption after experiencing perils, hence a promising strategy to reduce poverty. With the substantial amount of public funds that goes to PCIC, it is important to know whether its services bring positive impacts to small-scale farmers.The results of the impact evaluation showed that crop insurance had a positive impact on rice farmers during the period of observation. It increased access to credit, smoothened consumption, and increased net income from rice production. The impact on income is particularly pronounced among smaller farms. It is recommended that PCIC should expand to small farm holders to maximize the benefits of the crop insurance program.
Keywords: 330; Impact Evaluation; Crop Insurance; Rice farmers; Western Visayas